Bi-layer graphene structure with non-equivalent planes: Magnetic properties study. (May 2018) - Mhirech, A.; Aouini, S.; Alaoui-Ismaili, A.; Bahmad, L.
Abstract: In this paper, we study the magnetic properties of a ferromagnetic bi-layer graphene structure with non-equivalent planes. The geometry of the studied system is formed by two layers (A) and (B) consisting of the spins σ = 1 / 2 and S = 1 . For this purpose, the influence of the coupling exchange interactions, the external magnetic and the crystal fields are investigated and presented as well as the ground state phase diagrams. The Monte Carlo simulations have been used to examine the behavior of the partial and the total magnetizations as a function of the system parameters. These effects on the compensation and critical temperatures behavior are also presented in different phase diagrams, for the studied system. Highlights: In this work, we study the magnetic properties of two non-equivalent planes. We investigated the compensation and critical temperatures. The ground state phase diagrams are presented and discussed. A bi-layer graphene structure is studied using Monte Carlo simulations. The effect of the crystal field is examined and discussed.